THE PRINCIPLE OF SUCCESSION IN TEACHING ENGLISH LANGUAGE TO STUDENTS OF HIGHER SCHOOLS - Rybina, Nataliia; Koshil, Nataliia; Hyryla, Olha (Mountain School of Ukrainian Carpaty, 2023)
The article deals with the principle of succession in teaching English language to students of higher schools. The work highlights the importance of this principle in scaffolding students' learning and building a strong foundation of language skills. It also emphasizes the need for careful selection of appropriate teaching materials that are aligned with students' proficiency levels and learning objectives. Scaffolding techniques are discussed as essential for providing students with the necessary support and guidance to understand complex language structures and concepts. Assessment and feedback are also identified as playing a crucial role in tracking students' learning progress and providing constructive feedback to help them improve their language skills. Finally, the research suggests that the principle of succession is not only important for teaching English language to philological students but also for promoting learner autonomy and independence. Overall, the work aims to contribute to the existing body of knowledge on language teaching and learning and to inform language educators and policymakers on the best practices for teaching English language to students of philological specialties. The article also discusses the challenges and limitations associated with implementing the principle of succession in different educational contexts, such as teacher training, classroom management, and curriculum design. It highlights the importance of providing adequate training and professional development opportunities for language educators to help them effectively implement the principle of succession in their teaching practices. The study emphasizes the need for a studentcentered approach that takes into account students' individual needs, preferences, and cultural backgrounds. The article concludes by suggesting several prospects for further research in this area, including investigating the effectiveness of different scaffolding techniques, exploring the impact of the principle of succession on students' motivation and engagement, and examining the role of assessment and feedback in implementing this principle.